Pengaruh Perendaman Kalsium Klorida (CACL2) Terhadap Umur Simpan Buah Duku Segar - Arnold P. P. Rumajauw; Budi Santoso; Besse Amriati (Agrotek, 2012)
Agricultural production in Manokwari in 2007 showed that production duku reached an average production of 58.8 kw / ha (BPS Manokwari, 2008). Duku is one of horticultural products are susceptible to damage during storage. This study aims to assess the use of calcium chloride in an effort to extend the shelf life of fresh duku. The method used in this study is the experimental method with laboratory observation techniques. The study consisted of three treatments, namely: (1) control (duku not soaked), (2) treatment duku immersion in a solution of 3% CaCl2, and (3) treatment duku immersion in a solution of 6% CaCl2. The parameters observed weight of the fruit, the appearance of the fruit, the amount of production of carbon dioxide (CO2), and total dissolved solids. Giving the treatment of calcium chloride (CaCl2) can only inhibit the respiration rate and the rate of weight loss fruit, whereas for the other parameters do not provide satisfactory results. CaCl2 application method by immersion was not suitable to be applied on duku because it will trigger the growth of fungi that become shorter shelf-life than without CaCl2 treatment.